Antecedents and Consequences Psychological Contract Fulfillment - Sunarta Sunarta; Vigoureux Chinyabuuma Titho; Yunus Agung Kristanto; Rini Setyaningsih (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2022)
AbstractThis study aims to examine the role of psychological contract fulfillment in mediating the effect of achievement motivation and affective commitment on salesforce performance. The research was conducted on the dynamics and uncertainties of the post-global pandemic 2020. The study was done through a survey of 130 salesforces who are suppliers of retail businesses. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Square-PLS. The study results showed a direct influence of achievement motivation and affective commitment on sales performance and an indirect effect through the fulfillment of the psychological contract. Employees with high achievement motivation and higher affective commitment will be accompanied by efforts to fulfill psychological contracts that ultimately affect performance. The study’s findings risults provide potential implications for psychological contracts for more flexible work arrangements in dynamics and environmental uncertainty. Keywords:achievement motivation, affective commitment, salesforce performance, psychological contract fulfillment Anteseden dan Konsekuensi Pemenuhan Kontrak Psikologis AbstrakPenelitian ini bertujuan untuk menguji peran pemenuhan kontrak psikologis dalam memediasi pengaruh motivasi berprestasi dan komitmen afektif terhadap kinerja tenaga penjualan. Penelitian dilakukan pada kondisi dinamika dan ketidakpastian lingkungan post global pandemic 2020. Penelitian dilakukan melalui survei terhadap 130 tenaga penjualan yang merupakan pemasok usaha retail. Data dianalisis dengan Structural Equation Modelling (SEM) berbasis Partial Least Square. Hasil penelitian menemukan pengaruh langsung motivasi berprestasi dan komitmen afektif terhadap kinerja penjualan dan pengaruh tidak langsung melalui pemenuhan kontrak psikologis. Karyawan dengan motivasi berprestasi dan komitmen afektif yang lebih tinggi akan diiringi dengan upaya karyawan untuk memenuhi kontrak psikologis dan akhirnya berpengaruh terhadap kinerja. Hasil penelitian ini memberikan implikasi potensi kontrak psikologis untuk pengaturan kerja yang lebih fleksibel di tengah dinamika dan ketidakpastian lingkungan. Kata kunci:motivasi berprestasi, komitmen afektif, kinerja tenaga penjualan, pemenuhan kontrak psikologis